2016
DOI: 10.1093/dnares/dsw031
|View full text |Cite
|
Sign up to set email alerts
|

Z-DNA-forming sites identified by ChIP-Seq are associated with actively transcribed regions in the human genome

Abstract: Z-DNA, a left-handed double helical DNA is structurally different from the most abundant B-DNA. Z-DNA has been known to play a significant role in transcription and genome stability but the biological meaning and positions of Z-DNA-forming sites (ZFSs) in the human genome has not been fully explored. To obtain genome-wide map of ZFSs, Zaa with two Z-DNA-binding domains was used for ChIP-Seq analysis. A total of 391 ZFSs were found and their functions were examined in vivo. A large portion of ZFSs was enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 36 publications
4
83
0
Order By: Relevance
“…In addition, the instable GT microsatellite is part of a highly predicted Z-DNA region. Sequences transiently forming Z-DNAs are non-randomly distributed, occur more frequently proximal to transcription start sites, and influence promoter activity [46][47][48]. Self-and cross-co-activation of both the RG and CNS promoters by the reference protein and CNS-specific isoforms were consistent findings in our transient transfection studies of SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, the instable GT microsatellite is part of a highly predicted Z-DNA region. Sequences transiently forming Z-DNAs are non-randomly distributed, occur more frequently proximal to transcription start sites, and influence promoter activity [46][47][48]. Self-and cross-co-activation of both the RG and CNS promoters by the reference protein and CNS-specific isoforms were consistent findings in our transient transfection studies of SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 71%
“…The instable microsatellite region includes interspersed GC repeats. This region has a high potential for Z-DNA formation [45] known to frequently influence promoter activation [46][47][48]. To determine possible effects of the variable microsatellite on promoter activity, we amplified proximal CNS promoters (− 539 to + 63 bp relative to the transcription start site) differing in GT sizes, but otherwise containing identical sequences, from human subjects, cloned the fragments into reporter vectors, and transiently transfected the constructs into SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…Possibility of Z-DNA transition was also demonstrated for some genomic regions such as promoter zones with nucleosome removed by RNA polymerase or chromatin remodeling factors (1,8789). Treatment of cells with CBL0137 provides the necessary conditions for Z-DNA transition, i.e.…”
Section: Discussionmentioning
confidence: 91%
“…The idea that ADAR1 could interact with DNA structure dates back to original observations made by Rich and colleagues who suggested that the Z-alpha domain of ADAR1 recognizes an alternative left-handed DNA structure 12,13,34 . Over the years, a very strong case has been made for the existence of Z-DNA and its role in many biological processes, particularly transcriptional regulation [37][38][39][40] . Specifically, it has been reported that Z-DNA is related to both transcriptional activation 41,42 and inhibition 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been reported that Z-DNA is related to both transcriptional activation 41,42 and inhibition 43,44 . Mechanistically, this change in structure is thought to be coupled to transcription by the recruitment of transcription factors, such as PolII, for enhancement, or the direct blockade of the transcriptional machinery leading to PollI stalling during inhibition 37,39,[45][46][47] .…”
Section: Discussionmentioning
confidence: 99%